Streik als Mittel des Arbeitskampfes Das Tarifeinheitsgesetz und die Tarifautonomie - Blanke, Hermann-Josef; Conrad, Robert (Mohr Siebeck, 2019)
A series of strikes by German train drivers and pilots in 2015 marked the collective bargaining year and saw new regulations introduced. Taking the decision of the Federal Constitutional Court on collective bargaining unity, the contributions in this volume examine fundamental aspects of tariff agreements and autonomy as well as the right of labour organisations to strike and unions to use strikes as part of their traditional armoury.
PublicationDate: 20191127
Keywords: Beamtenstreik -- Koalitionsfreiheit -- Praxistheorie -- AG xxxAMPRxxx Co. KG -- Tarifeinheit -- Dionysius the Areopagite -- Shepherd of Hermas -- Tarifpluralität -- Streikkultur -- Verfassungsrecht und Staatslehre -- Arbeits- und Sozialrecht